2016
DOI: 10.1371/journal.pone.0163452
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Anatomical Research on the Operative Windows of Oblique Lumbar Interbody Fusion

Abstract: To provide applied anatomical evidence of the preoperative assessment of oblique lumbar interbody fusion (OLIF), the anatomical parameters of the OLIF operative window were observed through computed tomography angiography (CTA). We selected imaging data from 60 adults (30 males, 30 females) who underwent abdominal CTA and T12-S1 vertebral computed tomography (CT) with three-dimensional reconstruction. The OLIF operative windows at the L1-2, L2-3, L3-4, L4-5 and L5-S1 levels were as follows: the vascular window… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 17 publications
2
59
2
1
Order By: Relevance
“…Diana et al [24] analyzed 100 MR images of the lumbar spine to investigate the left-sided retroperitoneal oblique corridor of L2-S1 and got a conclusion of (1) 90% of the subjects had oblique access to each of the L2-L5 intervertebral discs and (2) only 69% had clear access to the L5-S1 intervertebral discs. Liu et al [25] analyzed 60 adults through abdominal computed tomography angiography and computed tomography of T12-S1 vertebral with three-dimensional reconstruction, then they deemed that the working corridor of each level related to OLIF has its own anatomical peculiarities, and not all levels are suitable for left-sided OLIF. And Chen et al [13] studied 400 subjects by lumbar spine MRI and concluded that OLIF in a left-sided approach can be suitable for the most Chinese patients from L2 to S1 segment; meanwhile, the more surgical space of the OLIF is seen in older female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Diana et al [24] analyzed 100 MR images of the lumbar spine to investigate the left-sided retroperitoneal oblique corridor of L2-S1 and got a conclusion of (1) 90% of the subjects had oblique access to each of the L2-L5 intervertebral discs and (2) only 69% had clear access to the L5-S1 intervertebral discs. Liu et al [25] analyzed 60 adults through abdominal computed tomography angiography and computed tomography of T12-S1 vertebral with three-dimensional reconstruction, then they deemed that the working corridor of each level related to OLIF has its own anatomical peculiarities, and not all levels are suitable for left-sided OLIF. And Chen et al [13] studied 400 subjects by lumbar spine MRI and concluded that OLIF in a left-sided approach can be suitable for the most Chinese patients from L2 to S1 segment; meanwhile, the more surgical space of the OLIF is seen in older female patients.…”
Section: Discussionmentioning
confidence: 99%
“…The oblique access corridor has been investigated by many researchers. Liu et al [4] selected imaging data from 60 adults who underwent abdominal CTA and T12-S1 vertebral computed tomography (CT) with three-dimensional reconstruction, and the vascular window, bare window, and psoas major window were [5] dissected 20 fresh-frozen fulltorso cadaveric specimens and examined the oblique anatomical corridor of the L2-S1 discs. All measurements of the anatomical corridor were defined as the left lateral border of the aorta (or iliac artery).…”
Section: Discussionmentioning
confidence: 99%
“…Its utility for correcting deformity has also been reported (7). Additionally, the use of transoperative neurophysiologic monitoring is not necessary (3).…”
Section: Advantages and Disadvantages Of The Lumbar Fusion Techniquesmentioning
confidence: 99%
“…Each technique has its advantages and disadvantages (1,2). OLIF is an emerging procedure that has progressively been used by spine surgeons (3,4). The retroperitoneal space allows direct access to the intervertebral space, thus avoiding injury to the paraspinal muscles, psoas muscle, and lumbar plexus (5,6).…”
Section: Introductionmentioning
confidence: 99%